Comparing the Learning Outcomes of Online versus Face-to-Face Formats in Teaching a Marketing Course: An Empirical Observation - Choe, Sang T. (Archives of Business Research, 2023)
A study was conducted to compare the academic performance of two groups of university students enrolled in the Principles of Marketing course. One group of students participated in an online class, while the other group of students attended a face-to-face class. The results of the study revealed notable differences in academic performance between the two groups. The findings consistently indicated that the online students outperformed their counterparts in the face-to-face class, particularly, in the multiple-choice examinations as well as the essay-problem questions. However, the author of the study highlights a significant factor that readers should consider when interpreting these results. The higher performance demonstrated by online students may be attributed to their demographic and socioeconomic background. It was observed that the online students were significantly older, married, and came from a higher economic status compared to the face-to-face class students. Furthermore, the online students devoted nearly double the amount of time to studying, averaging 6.26 hours per week compared to 3.54 hours for the face-to-face class students in the study.